2019
DOI: 10.1080/1051712x.2019.1565137
|View full text |Cite
|
Sign up to set email alerts
|

When Does Relational Exchange Matters? Social Bond, Trust and Satisfaction

Abstract: The extant literature on business-to-business relationship has shown that trust, relationship duration, and social bond are the key drivers of relationship satisfaction.Notwithstanding, studies on the examination of when and why these variables translate into successful relationship are still scarce and need further exploration. This research investigates the conditions under which trust and social bonds influence satisfaction in a business-to-business relationship.Design/methodology/approach: The data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 93 publications
(128 reference statements)
2
24
0
2
Order By: Relevance
“…This feature may also be what is lacking the most in the public case, making it a more decisive factor in explaining the suppliers’ satisfaction variance. This interpretation is supported by recent research that found that, particularly with long-term relations, social bonds increase supplier satisfaction (Shanka and Buvik, 2019). Hence, the short-term nature of relations imposed by tendering laws again put public organisations at a disadvantage.…”
Section: Discussion and Implications: Public Organisations’ Choice For Relational Leverssupporting
confidence: 61%
See 1 more Smart Citation
“…This feature may also be what is lacking the most in the public case, making it a more decisive factor in explaining the suppliers’ satisfaction variance. This interpretation is supported by recent research that found that, particularly with long-term relations, social bonds increase supplier satisfaction (Shanka and Buvik, 2019). Hence, the short-term nature of relations imposed by tendering laws again put public organisations at a disadvantage.…”
Section: Discussion and Implications: Public Organisations’ Choice For Relational Leverssupporting
confidence: 61%
“…A theory that has been successfully used to explain B2B exchange relationships and that has been applied in the attractiveness research and that seems to be promising in explaining the preferential treatment phenomenon and how to mobilise supplier resources for a particular buying firm’s benefit is social exchange theory (Lambe et al , 2001; Schiele et al , 2012; Reichenbachs et al , 2017; Pulles et al , 2019; Shanka and Buvik, 2019). Social exchange theory is based on the idea of expectations leading to exchanges (in the buyer-supplier case, these positive expectations that a supplier has towards the buyer have been termed customer attractiveness), which is then evaluated against a standard (leading to supplier satisfaction, in the positive case of the buyer’s performance matching the standard applied by the supplier).…”
Section: Preferred Customership: Benefits Theory and Evidencementioning
confidence: 99%
“…Shared norms and values, based on previous business experiences and transactions, can lead to a shift in costbenefit analyses that emphasize mutual interests rather than self-interests (Heide & John, 1992;Zaheer & Venkatraman, 1995). This also leads to behaviors in relational exchange that are more likely to be controlled through internal mechanisms, in the form of mutual behavioral expectations or personal relations, rather than incentives, as in market governance, or fiat, as in vertical integration (Dwyer et al, 1987;Joshi & Stump, 1999;Lambe et al, 2001;Morgan & Hunt, 1994;Shanka & Buvik, 2019).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The research analysis showed that the supplier satisfaction brings significant impact on their commitment with the customers. Another study by as in [32] investigated the relationship between the supplier level satisfaction and the commitment of supplier in long run. For this study, they collected data from 159 producers of footwear through structured questionnaire.…”
Section: H3 Time Management Quality Has Significant Effect On Supplier Satisfactionmentioning
confidence: 99%